5.1. Characteristic equation has one double root 1. Hence the general solution of the corresponding homogeneous equation is C1 et + C2 tet . We look for a particular solution of the non-homogeneous equation in the form y(t) = t2 (At + B)et + C. We have y 0 = (3At2 + 2Bt)et + (At3 + Bt2 )et = (At3 + (3A + B)t2 +2Bt)et and y 00 = (3At2 +2(3A+B)t+2B)et +(At3 +(3A+B)t2 +2Bt)et = (At3 + (6A + B)t2 + (6A + 4B)t + 2B)et . Substituting this into the equation we get (At3 +(6A+B)t2 +(6A+4B)t+2B)et −2(At3 +(3A+B)t2 +2Bt)et +(At3 +Bt2 )et +C = ((6A + B − 6A − 2B + B)t2 + (6A + 4B − 4B)t + 2B)et + C = 6Atet + 2Bet + C = tet + 4, which implies that A = 1/6, B = 0, C = 4, so that the general solution is 1 y(t) = (C1 + C2 t)et + t3 et + 4. 6 Its derivative is y 0 (t) = C2 et + (C1 + C2 t)et + 12 t2 et + 16 t3 et . Substituting the initial condition, we get C1 + 4 = 1, C2 + C1 = 1. We get C1 = −3 and C2 = 4. Consequently, the solution of the initial value problem is 1 3 y(t) = t + 4t − 3 et + 4. 6 5.2. The unique repeated root of the characteristic polynomial is λ = −2. It follows that a fundamental system of solutions of the homogeneous equation is y1 (t) = e−2t and y2 (t) = te−2t . We are looking for a solution of the nonhomogeneous equation in the form y = u1 (t)y1 (t) + u2 (t)y2 (t) from the system 0 u1 y1 + u02 y2 = 0 u01 y10 + u02 y20 = t−2 e−2t It our case it is −2u01 e−2t + u01 e−2t + 0 u2 (−2te−2t u02 te−2t = 0 + e−2t ) = t−2 e−2t It is equivalent to u01 + u02 t −u01 + u02 (−t + 1/2) = 0 = t−2 /2 Adding the two equations, we get u02 /2 = t−2 /2, or u02 = t−2 . 1 Then from the first equation we get u01 = −u02 t = −t−1 . Integrating u0i , we get u2 (t) = −t−1 + C2 . u1 (t) = − ln t + C1 , It follows that the general solution of the equation is y(t) = − ln t · e−2t − e−2t + C1 e−2t + C2 te−2t . κ κ 5.3. Equation of the motion of a spring is u00 + m u = 0, where m can be g κ found from equality m = L , where g is acceleration of free fall, and L is the length by which the spring is stretched. We get therefore, equation (we use feet and seconds) 32 u = 0. u00 + 0.5 The initial condition is u(0) = 0.25 and u0 (0) = 0. The characteristic polynomial is λ2 + 64. It follows that the general solution is u(t) = C1 sin 8t + C2 cos 8t. Then u0 (t) = 8C1 cos 8t − 8C2 sin 8t. The initial condition gives C2 = 0.25 and C1 = 0. Hence, after t seconds, the mass will be down from the equilibrium position by 0.25 cos 8t feet, i.e., by 3 cos 8t inches. It follows that period of motion is 2π/8 = π/4 seconds, amplitude is 6 inches, and frequency is 4/π sec−1 F , where F is the external force, and m is 5.4. The equation is u00 + Lg u = m the mass. We get therefore u00 + 2 cos 3t 32 u= , 0.125 4 or 1 cos 3t. 2 The initial condition is u(0) = 1/6, u0 (0) = 0. 5.5. We have to find the integral Z ∞ t sin at e−st dt. u00 + 162 u = 0 R Let at first the indefinite integrals I1 = sin at e−st dt and I2 = R us find cos at e−st dt, where a and s are parameters. Using integration by parts, we get Z Z 1 1 1 a −st −st a I1 = − sin at de = − sin at e + cos at e−st dt = − sin at e−st + ·I2 , s s s s s and 1 I2 = − s Z −st cos at de 1 a = − cos at e−st − s s Z 1 a sin at e−st dt = − cos at e−st − ·I1 . s s Substituting the second equation into the first, we get 1 1 a 1 a a2 −st a −st I1 = − sin at e + − cos at e − · I1 = − sin at e−st − 2 cos at e−st − 2 ·I1 , s s s s s s s 2 hence I1 = 1+ a2 s2 −1 1 a − sin at e−st − 2 cos at e−st s s = −s sin at − a cos at −st e s2 + a2 Substituting this into the second equation, we get 1 a s sin at + a cos at −st e = I2 = − cos at e−st + · s s s2 + a2 −(s2 + a2 ) cos at + as sin at + a2 cos at −st a sin at − s cos at −st e e = 2 2 s(s + a ) s2 + a2 Z Let us compute now the integral Z Z s a s sin at + a cos at −st e dt = tI1 + 2 I1 + 2 I2 t sin at e−st dt = t dI1 = tI1 + s2 + a2 s + a2 s + a2 a s We have I1 (0) = − s2 +a As t → ∞, I1 and I2 converge 2 , I2 (0) = − s2 +a2 . exponentially to 0. It follows that Z 0 ∞ ∞ a s = I1 + 2 I2 t sin at e dt = tI1 + 2 2 2 s +a s +a t=0 s a a s 2as 0− − 2 · 2 − 2 · 2 . = 2 2 2 2 2 s +a s +a s +a s +a (s + a2 )2 −st 3